"Liberty to the downtrodden" : Thomas L. Kane, romantic reformer - Grow, Matthew J. (Lamar series in western history., 2009)
Thomas L. Kane (1822-1883), a crusader for antislavery, women's rights, and the downtrodden, rose to prominence in his day as the most ardent and persuasive defender of Mormons' religious liberty. Thou